Penetapan Parameter Standar dan Skrining Fitokimia Simplisia Batang Sereh (Cymbopogon citratus) - Lailatul Taqbi Rahmatya; Umi Yuniarni; Bertha Rusdi (Bandung Conference Series: Pharmacy, 2024)
Abstract. Lemongrass is a plant that has many uses in traditional medicine in addition to kitchen spices, kitchen lemongrass is also useful as a remedy for headaches, body warming, cough, stomach pain, diarrhea, heat reduction, and mosquito repellent. The purpose of this study is to obtain standard values of parameters and phytochemical screening of kitchen lemongrass stems (Cymbopogon citratus). This study uses laboratory experimental research methods by testing specific parameters in the form of water-soluble and ethanol-soluble juice levels, non-specific parameters in the form of drying shrinkage, moisture content, and specific weight, as well as phytochyma screening referring to the Pharmacopoeia Indonesia Herbal. The results of the standard parameters of lemongrass stem water soluble juice content were 30.61%, ethanol soluble juice content was obtained 26.44%, drying shrinkage of lemongrass stem was 6.91%, moisture content was 9.19%, 9.85% and specific weight was obtained of 0.85 g/mL. The results of phytochemical screening screening of lemongrass stem simplicia contain a group of alkaloid compounds, flavonoids, polyphenolates, saponins, tannins, monoterpenoids and sesquiterpenoids. Abstrak. Sereh merupakan tanaman yang memiliki banyak digunakan dalam pengobatan tradisional selain untuk bumbu dapur sereh dapur juga bermanfaat sebagai obat untuk sakit kepala, penghangat badan, batuk, nyeri lambung, diare, penurun panas, dan pengusir nyamuk. Tujuan penelitian ini untuk memperoleh nilai-nilai standar parameter dan skrining fitokimia batang sereh dapur (Cymbopogon citratus). Penelitian ini menggunakan metode penelitian eksperimental laboratorium dengan menguji parameter spesfik berupa kadar sari larut air dan larut etanol, parameter non spesifik berupa susut pengeringan, kadar air, dan bobot jenis, serta skrining fitokima yang merujuk pada Farmakope Herbal Indonesia. Hasil parameter standar batang sereh kadar sari larut air sebesar 30,61%, kadar sari larut etanol diperoleh 26,44%, susut pengeringan batang sereh sebesar 6,91%, kadar air sebesar 9,19%, 9,85% dan bobot jenis diperoleh sebesar 0,85 g/mL. Hasil penapisan skrining fitokimia simplisia batang sereh mengandung golongan senyawa alkaloid, flavonoid, polifenolat, saponin, tanin, monoterpenoid dan sesquiterpenoid.